Membangun Karakter Peduli Lingkungan Melalui Penanaman 1000 Pohon Di Kelurahan Muara Lembu Kecamatan Singingi Kabupaten Kuantan Singingi - Yogi Riyantama Isjoni; Muhammad Syahrul Nizam; Rezika Nur Hiqmah; Mutia Andiva; Khairunnisa Dwi Nofrianti; Mutia Fajri; Ahmad Fadhil Arkan; Kenji Rye; Nurul Aini; Putri Alisa (Jurnal Insan Pengabdian Indonesia, 2023)
Kukerta students from the University of Riau 2023 engaged in community service activities for 40 days in the Muara Lembu sub-district, Singingi sub-district, Kuantan Singingi district. The objective of these activities was to cultivate an environmentally conscious mindset within the local community. To achieve this, the students planted a total of 1000 trees across various locations such as government agencies, schools, and sports centers in the Muara Lembu sub-district. The primary aim of this initiative was to restore green areas within the community and enhance awareness regarding the surrounding environment. This endeavor sought to foster a sense of responsibility among the residents of the Muara Lembu sub-district toward preserving and safeguarding the environment. Additionally, tree planting served as a means of mitigating potential disasters by contributing to water retention and erosion prevention in the Muara Lembu sub-district. As a result of these efforts, 1000 seedlings were successfully planted to contribute towards the preservation of the environment in the Muara Lembu sub-district.